Pembuatan Bahan Kemasan Mampu Urai Hayati (Biodegradable Packaging) Dari Tepung Tapioka - Budi Utami; Wiwik Pudjiastuti (Balai Besar Kimia dan Kemasan, 1996)
Experiment of biodegradable packaging from cassava starch has been done in a laboratory scale by preparing 9 formulation containing several type of substances. Physical properties and biodegradability from each formulation have been evaluated. Comparing with TIS Z 1707 - 1975, formulation 7 has the best physical properties using for food packaging with thickness= 0,15 mm, tensile strength= 189,39 kg£'cm2, elongation= 112,919 °!CJ, = 43,29 glm2. 24 hr and biodegradability = 2 weeks.